Metabolic Risk Factors, Leisure Time Physical Activity, and Nutrition in German Children and Adolescents. (19th June 2012) - Haas, Gerda-Maria; Liepold, Evelyn; Schwandt, Peter
Abstract : Purpose . We assessed the five components of the metabolic syndrome (MetS) as defined by the International Diabetes Federation (IDF) in 6040 (3158 males) youths aged 6–16 years who participated in the Präventions-Erziehungs-Programm (PEP Family Heart Study) in Nuernberg between 2000 and 2007. The purpose of this cross-sectional study was to examine associations with lifestyle habits. Results and Discussion . The prevalence of MetS was low in children (1.6%) and adolescents (2.3%). High waist circumference (WC) and low HDL-C were slightly higher in females (9.5% and 7.5%, resp.) than in males (8.8% and 5.7%, resp.). Low leisure time physical activity (LTPA) was significantly associated with low HDL-C (odds ratio [OR] 2.4; 95% CI 1.2–5.0) and inversely associated with hypertension (r = − 0.146 ), hypertriglyceridemia (r = − 0.141 ), and central adiposity (r = − 0.258 ). The risk for low HDL-C (≤1.3 mmol/L) was 1.7-fold (CI 1.0–2.6) higher in youth with high (≥33%) saturated fat consumption. A low polyunsaturated/saturated fat ratio (P/S ratio) was significantly associated with fasting hyperglycemia (OR 1.4; 95% CI 1.0–1.2).